2020
DOI: 10.1093/geront/gnaa061
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Frailty Trajectories: Their Shape and Influencing Factors

Abstract: Background and Objectives Frailty describes an increased vulnerability to adverse events such as disease or injury. Combatting this state remains a major challenge for geriatric research. By exploring how and why frailty changes throughout later life we will be better positioned to improve ways of identifying and treating those at high risk. Research Design and Methods We systematically reviewed publications that captured rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 43 publications
4
69
0
1
Order By: Relevance
“…Emerging evidence supports heterogeneity in frailty progression in aging with variations in individual rates of change [3,8]. Previous studies using different definitions of frailty as well as methodological approaches have reported both stable and declining trajectories in older adults [8][9][10][11][12]. But these findings regarding different frailty courses were not cross-validated in independent samples, and none have explored the underlying biology of latent subpopulations of frailty trajectories [8,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence supports heterogeneity in frailty progression in aging with variations in individual rates of change [3,8]. Previous studies using different definitions of frailty as well as methodological approaches have reported both stable and declining trajectories in older adults [8][9][10][11][12]. But these findings regarding different frailty courses were not cross-validated in independent samples, and none have explored the underlying biology of latent subpopulations of frailty trajectories [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using different definitions of frailty as well as methodological approaches have reported both stable and declining trajectories in older adults [8][9][10][11][12]. But these findings regarding different frailty courses were not cross-validated in independent samples, and none have explored the underlying biology of latent subpopulations of frailty trajectories [8,12]. Identifying trends and trajectories is acknowledged as a high priority for frailty research [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…This could have important implications for public health intervention strategies for the care of elderly people. A recent systematic review ( Welstead et al, 2020 ), concluded that, in lieu of a gold standard frailty measurement tool, it may be beneficial to utilise multiple measures. Subsequently, we used both the FI and the Fried phenotype to assess associations with inflammation and evaluate any potential differences in findings according to the measure used.…”
Section: Introductionmentioning
confidence: 99%
“…Although the concept of frailty is based on reversibility, many previous studies have focused on risk factors and protective factors for frailty [28]. Many studies have identified risk factors for frailty, including age, sex (female), cognitive ability (executive function, etc.…”
Section: Discussionmentioning
confidence: 99%
“…socioeconomic factors (financial stress, etc.) [28]. Conversely, the rate of recovery from frailty has not been investigated sufficiently, and the manifestation of frailty has been limited to physical frailty [29][30][31].…”
Section: Plos Onementioning
confidence: 99%